Prevalence and Risk Factors of Preterm Birth Among Pregnant Women Admitted at the Labor Ward of the Komfo Anokye Teaching Hospital, Ghana - Enoch Odame Anto; Enoch Odame Anto; Wina Ivy Ofori Boadu; Stephen Opoku; Ebenezer Senu; Valentine Christian Kodzo Tsatsu Tamakloe; Augustine Tawiah; Frank Ankobea; Emmanuel Acheampong; Emmanuel Acheampong; Agartha Odame Anto; Michael Appiah; et al. (Frontiers Media S.A., 2022)
Preterm birth is a global epidemic and a leading cause of neonatal mortality in Sub-Saharan Africa. We evaluated the prevalence and risk factors of preterm birth among women attending the labor ward for delivery at a tertiary hospital in Ghana. This comparative cross-sectional study was conducted among a cohort of 209 pregnant women admitted to the labor ward of the Komfo Anokye Teaching Hospital (KATH). Pregnant women who delivered between 28 and 36 completed weeks of gestation were classified as preterm delivery whereas those who delivered after 37-42 completed weeks were described as term. Sociodemographic, clinical, and obstetric data were collected from patient's folder and hospital archives. Categorical variables were analyzed and expressed as frequencies and proportions. We determined the association between obstetric factors and preterm delivery with multiple logistic regressions. Significance level of the strength of association was determined at p-value < 0.05. of the 209 participants, the prevalence of preterm birth was 37.3% (78/209) whereas 62.7% (131/209) delivered at Term. Intrauterine growth restriction (IUGR) [aOR = 2.15, 95% CI = (1.819.55), p = 0.0390], HELLP (hemolysis, elevated liver enzymes and low platelet count) syndrome [aOR = 3.94, 95% CI = (1.64-9.48), p = 0.0020], early gestational obesity [aOR = 2.11, 95% CI = (1.31-11.92), p = 0.0480] and preeclampsia [aOR = 4.56, 95% CI = (1.63-12.76), p = 0.004] were identified as independent risk factors of preterm birth. Prevalence of preterm birth was high among women attending labor admission at the Komfo Anokye Teaching Hospital and this was independently influenced by IUGR, HELLP syndrome, early gestational obesity, and preeclampsia. Identifying early signs of adverse pregnancy outcomes would inform the need for management policy to prevent high prevalence of preterm births.